Hikui disease in nine koi carp (Cyprinus carpio): first description of a cutaneous perivascular wall tumour. Issue 4 (16th June 2016) - Sirri, Rubina; Pretto, Tobia; Montesi, Francesco; Berton, Valeria; Mandrioli, Luciana; Barbé, Tim
Abstract : Background: Hikui disease is a well known disfiguring disease of koi carp ( Cyprinus carpio ) primarily affecting fish with red pigmentation. It causes light orange to golden yellow, multifocal to coalescing raised patches, starting from the red cutaneous areas. Some cases respond to surgery or topical treatment, but recurrence is common. Objectives: To describe the clinical and pathological presentation of Hikui disease and its cause. Animals: Nine affected koi carp belonging to private hobbyists. Methods: Eight fish underwent surgery or biopsy; one was euthanized. Tissues were submitted for histology, immunohistochemistry and transmission electron microscopy. Results: Five fish showed typical lesions of Hikui disease, whereas four fish showed an atypical presentation characterized by focal or multifocal, oedematous, dark red cutaneous plaques or nodules. Histology showed unencapsulated, infiltrating and densely cellular neoplasms composed of spindle cells arranged in bundles, rows and whorls frequently centred on capillaries. Immunohistochemistry for smooth muscle actin labelled neoplastic cells in all cases. Ultrastructure showed neoplastic cells with slender cytoplasmic processes encircling the capillaries, a thin basal membrane and occasional plasmalemmal vesicles. Conclusions and clinical importance: All of the data supported a neoplastic process producing perivascular wall tumours. Immunoreactivity to smooth muscle actin and the ultrastructural features were indicative of a pericyte origin (haemangiopericytoma). This is the first report dealing with Hikui disease that has achieved a conclusive diagnosis. The neoplastic nature of this condition suggests the potential usefulness of a surgical approach in the clinical management of less severe cases. Abstract : Background ‐ Hikui disease is a well‐known disfiguring disease of koi carp ( Cyprinus carpio ) primarily affecting fish with red pigmentation. It causes light orange to golden yellow, multifocal to coalescing raised patches, starting from the red cutaneous areas. Some cases respond to surgery or topical treatment, but recurrence is common.Objectives ‐ To describe the clinical and pathological presentation of Hikui disease and its cause.Conclusions and clinical importance ‐ All of the data supported a neoplastic process producing perivascular wall tumours. Immunoreactivity to smooth muscle actin and the ultrastructural features were indicative of a pericyte origin (haemangiopericytoma). This is the first report dealing with Hikui disease that has achieved a conclusive diagnosis. The neoplastic nature of this condition suggests the potential usefulness of a surgical approach in the clinical management of less severe cases.